REVISITING THE MYTHS IN ORHAN PAMUK’S THE RED HAIRED WOMAN - K., Nalini Selvi; T., Jayakumar (International Journal of Psychosocial Rehabilitation, 2020)
The novel The Red Haired Woman tells the story of Cem, an Istanbul boy whose life is turned upside-down when his father, a pharmacist, abandons the boy and his mother and disappears, offering no clues about where he’s headed. Without his father’s income, the family’s finances are doomed, and Cem must find work wherever he can to pay for his education. He soon lands on a temporary job as an apprentice to Mahmut, a welldigger, and just as quickly casts the older man as a replacement for his missing father, which leads to some mixed feelings. The adult Cem becomes obsessed with the story of Oedipus, who famously killed his father and married his mother, and the Persian story of a warrior who kills his son during a battle. Pamuk waxes Freudian theory, and it will not be a problem if Cem’s obsessions are not so repetitively alluded to.